The idea of justice - Sen, Amartya (Belknap Press of Harvard University Press, 2009)
Presents an analysis of what justice is, the transcendental theory of justice and its drawbacks, and a persuasive argument for a comparative perspective on justice that can guide us in the choice between alternatives